日本の高齢者におけるScreening Tool for Older Person's appropriate Prescriptions in Japanese（STOPP-J）リスト掲載薬の処方実態：レセプト情報・特定健診等情報データベース（NDB）を用いた記述疫学研究 - 加藤, 源太; 山本, 洋介; 佐藤, 泉美; 中山, 健夫; 福原, 俊一; 王, 睿; 大寺, 祥佑 (日本薬理学会年会要旨集, 2020)
National Database of Health Insurance Claims and Specific Health Checkups of Japan (NDB) is the largest insurance claim database in Japan. The aim of NDB is to analyze health care services provided by health insurance in Japan based on the Act on Assurance of Medical Care for Elderly People (2008). At the end of 2014, approximately 90% of all the health insurance claims were stored in NDB. In the present study, we described the proportion of prescription of drugs listed in Screening Tool for Older Person's appropriate Prescriptions in Japanese (STOPP-J) as those that require careful administration in older adults, using the data from NDB. Participation was limited to those who were aged equal to or more than 75 years and received any medical care provided by health insurance during the 2010-2014 period. Results suggest that more than 60% of the subjects had experiences to be regularly prescribed at least one of the drugs listed in STOPP-J. Although the prescriptions which examined in the present study do not mean inappropriate medications, further considerations for types of drugs might be required when doctors prescribe some drugs for older patients in actual clinical settings.